2013
DOI: 10.1002/jbm.a.35065
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun biodegradable polyorganophosphazene fibrous matrix with poly(dopamine) coating for bone regeneration

Abstract: Biodegradable polyphosphazenes were categorized as osteoinductive materials because of their phosphorus-containing feature; however, they were less supportive in cell attachment and proliferation at earlier points in comparison with biodegradable aliphatic polyesters. Therefore, mussel-inspired surface modification of poly(alanine ethyl ester-co-glycine ethyl ester)phosphazene (PAGP) was studied, intending to circumvent the above-mentioned disadvantage of polyphosphazene. To this end, PAGP and poly(L-lactide) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…The other possible reason for the reduced cell proliferation is relatively high concentration of dopamine (∼0.8 M). Generally, the addition of dopamine increased the cell proliferation when the dopamine used to generate poly(dopamine) coating with low dopamine concentration (<0.02 M) . In contrast, the cell proliferation was slightly reduced when the dopamine used as a cross‐linker with high concentration as in this study (>0.5 M) .…”
Section: Resultsmentioning
confidence: 48%
“…The other possible reason for the reduced cell proliferation is relatively high concentration of dopamine (∼0.8 M). Generally, the addition of dopamine increased the cell proliferation when the dopamine used to generate poly(dopamine) coating with low dopamine concentration (<0.02 M) . In contrast, the cell proliferation was slightly reduced when the dopamine used as a cross‐linker with high concentration as in this study (>0.5 M) .…”
Section: Resultsmentioning
confidence: 48%
“…Secondly, the MBGs are hydrophilicity and have large specific area and pore structure, which may enhance the hydrophilicity of the coating materials. In the study of Li Yan, after the dopamine solution treatment, the water contact angles of as‐spun PAGP and PLLA decreased . Here, we put an example of increased hydrophobicity via dopamine coating.…”
Section: Resultsmentioning
confidence: 82%
“…Blank domains with no coating material could be found when DA solution of low concentration was used, whereas excess patches could be found if the DA solution had a relatively high concentration. In previous studies, it was found that a DA solution of 2 mg/ml was quite efficient in obtaining a homogenous PDA surface layer by coating PDA on fiber post [33] or polymeric nanofibers [34]. Therefore, with all the morphological comparisons on PDA-modified glass fibers in Fig.…”
Section: Pda Coating On Glass Fibersmentioning
confidence: 96%